Morphological description of the immatures of the ant, Monomorium floricola - Solis, Daniel Russ [UNESP]; Fox, Eduardo Gonçalves Paterson [UNESP]; Kato, Luciane Mayumi; de Jesus, Carlos Massuretti [UNESP]; Yabuki, Antonio Teruyoshi [UNESP]; de Carvalho Campos, Ana Eugênia; Bueno, Odair Correa [UNESP] (My University, 2010)
Some ant species of the genus Monomorium Mayr occur worldwide and are considered important urban pests. The larvae of only a few species of this genus have been described, and these descriptions are either superficial or incomplete. This study aimed to determine the number of larval instars and describe the immature stages of the ant Monomorium floricola Jerdon (Formicidae: Myrmicinae). Specimens were analyzed and measured using light and scanning electron microscopy. Three larval instars were found, and all larvae had pheidoloid bodies with ectatommoid mandibles, consistent with other Monomorium species described previously. Five types of body hairs were described, and their distribution was instar-specific. Body and mandible dimensions of the larvae also were constant for each instar. Like other Myrmicinae, the larvae did not create a cocoon. Some of differences among the hair types and sensilla were observed by comparing the samples with larvae of other species in the genus, and these differences may have taxonomic utility.
Keywords: Larval instars; Myrmicinae; Solenopsidini; Tramp species